Factor Structure, Psychometric Properties, and Measurement Invariance of the Pandemic Experiences and Perceptions Scale Among Italian Hospital Workers - Portoghese, Igor; Galletta, Maura; Leiter, Michael P.; Piras, Ilenia; Lecca, Luigi Isaia; Puligheddu, Monica; Campagna, Marcello (La Medicina del Lavoro, 2024)
Background: The COVID-19 pandemic represented substantial risks to hospital workers’ physical and mental health. The availability of validated measures on the impact of the pandemic on workplaces is crucial for developing data-driven interventions. The primary purpose of our study was to translate it into Italian and assess factor structure, psychometric properties, and measurement invariance of the Pandemic Experiences and Perceptions Scale (PEPS). Methods: The survey was completed by 766 workers from an Italian hospital. We examined the internal structure of the PEPS using confirmatory factor analyses (CFA) and exploratory structural equation modeling (ESEM) techniques and testing the invariance for clinical vs. nonclinical workers. Results: The six-factor ESEM solution showed an excellent fit to the data (CFI=0.956, TLI=0.932, RMSEA=0.050), supporting the superiority of the ESEM solution. The factorial invariance of the PEPS across occupational roles (clinical vs. nonclinical hospital workers) was supported, and the ESEM-based McDonald’s omega was good for all factors.Conclusions: The results from this study provided evidence for the factorial validity, reliability, and measurement invariance across occupational roles of the Italian version of the PEPS. Thus, the Italian version of the PEPS is a reliable and valid tool for assessing pandemic experiences and perceptions among Italian workers.